Internal government supervision in improving accountability for forward village financial management in North Lampung - Erwinsyah, Muhammad; Supriatna, Tjahya; Djohan, Djohermansyah; Sartika, Ika (International Journal Labs, 2023)
The aim of this research is to analyze and determine the supervision of financial management in developed villages, the supporting and inhibiting factors for the supervision of financial management in developed villages and the government's internal supervision model in increasing accountability for financial management in developed villages in North Lampung Regency, Lampung Province. This research uses the supervision theory proposed by Ndraha. The research method used is a qualitative approach with descriptive research type. The data analysis technique used is data reduction and drawing conclusions. The research results show that the village government has understood the supervision standards for village fund management which have been adjusted by referring to the regulations set by the central government which have substantially determined the scope, mechanisms, actors, officials, monitoring tools and funding/financing of supervision in the regions. Performance measurement has been running constantly and continuously because changing regulations require regular supervision and village funds, this is demonstrated by the existence of technical regulations issued by the government and adapted to regional needs. The government's internal monitoring model in increasing the accountability of advanced village financial management in North Lampung Regency, Lampung Province, through the SIMONDes application in order to provide sanctions and rewards related to government accountability and village finances.